Economic Uncertainty and the Effectiveness of Monetary Policy - Knut Are Aastveit; Gisle James Natvik; Sergio Sola (Norges Bank, 2013)
This paper explores if economic uncertainty alters the macroeconomic influence of monetary policy. We consider several measures of U.S. economic uncertainty, and estimate their interaction effects with monetary policy shocks as identified through structural vector autoregressions. We find that monetary policy shocks affect economic activity considerably weaker when uncertainty is high, consistently with "real-options" effects suggested by models with non-convex adjustment costs. Investment responds two to five times weaker when uncertainty is in its upper instead of its lower decile. High U.S. uncertainty is associated with lower policy influence not only domestically, but in Canada too.
hdl:11250/2496690
Keywords: E30; E32; E37; 330; structural VAR; uncertainty; monetary policy